The Japanese Culture of Mourning Whales Whale Graves and Memorial Monuments in Japan - Itoh, Mayumi (Springer Singapore, 2018)
This book provides an in-depth study of Japanese whaling culture, emphasizing how the Japanese have considered whales and whaling in relation to their understanding of nature and religion. It examines why and how the Japanese have mourned the deaths of whales, treating them as if they were human beings, and assesses the relevance of this culture to nature conservation and management of sustainable use of natural resources. It also sheds new light on Japanese whaling, one of the most controversial issues in the contemporary world, by highlighting the hitherto unknown aspects of Japanese beliefs about whales and whaling, which constitute an integral part of their core concept of how they should coexist with nature. Through cross-examining previous studies of Japanese whaling, as well as analyzing new documents and conducting field research on location, this book presents a comprehensive survey of Japanese whaling culture and memorial rites for whales and offers viable insights on how the Japanese whaling culture can be applied to solving current global issues, including nature conservation, management of sustainable use of natural resources, and protection of wildlife and its habitats.